Association of adenovirus 36 infection with obesity-related gene variants in adolescents - Dušátková, L; Zamrazilová, H; Aldhoon Hainerová, I; Atkinson, R L; Sedláčková, B; Lee, Z P; Včelák, J; Bendlová, B; Kunešová, M; Hainer, V (Physiological research, 2015)
Both, common gene variants and human adenovirus 36 (Adv36) are involved in the pathogenesis of obesity. The potential relationship between these two pathogenic factors has not yet been investigated. The aim of our study was to examine the association of obesity susceptibility loci with Adv36 status. Genotyping of ten gene variants (in/near TMEM18, SH2B1, KCTD15, PCSK1, BDNF, SEC16B, MC4R, FTO) and analysis of Adv36 antibodies was performed in 1,027 Czech adolescents aged 13.0-17.9 years. Variants of two genes (PCSK1 and BDNF) were associated with Adv36 seropositivity. A higher prevalence of Adv36 antibody positivity was observed in obesity risk allele carriers of PCSK1 rs6232, rs6235 and BDNF rs4923461 vs. non-carriers (chi(2)=6.59, p=0.010; chi(2)=7.56, p=0.023 and chi(2)=6.84, p=0.033, respectively). The increased risk of Adv36 positivity was also found in PCSK1 variants: rs6232 (OR=1.67, 95 % CI 1.11-2.49, p=0.016) and rs6235 (OR=1.34, 95 % CI 1.08-1.67, p=0.010). PCSK1 rs6232 and BDNF rs925946 variants were closely associated with Adv36 status in boys and girls, respectively (chi(2)=5.09, p=0.024; chi(2)=7.29, p=0.026). Furthermore, PCSK1 rs6235 risk allele was related to Adv36 seropositivity (chi(2)=6.85, p=0.033) in overweight/obese subgroup. In conclusion, our results suggest that obesity risk variants of PCSK1 and BDNF genes may be related to Adv36 infection.
Keywords: Female; ženské pohlaví; Proprotein Convertase 1; Adolescent; Obesity; adenovirové infekce lidí; lidé; Genetic Variation; Adenovirus Infections, Human; genetické asociační studie; obezita; Male; Brain-Derived Neurotrophic Factor; Adenoviridae; mozkový neurotrofický faktor; mužské pohlaví; proproteinkonvertasa 1; genetická variace; mladiství; Genetic Association Studies; Humans